Methylation of the circadian Clock gene in the offspring of a free-living passerine bird increases with maternal and individual exposure to PM10. (January 2017) - Romano, Andrea; De Giorgio, Barbara; Parolini, Marco; Favero, Chiara; Possenti, Cristina Daniela; Iodice, Simona; Caprioli, Manuela; Rubolini, Diego; Ambrosini, Roberto; Gianfranceschi, Luca; Saino, Nicola; Bollati, Valentina
Abstract: The consequences of exposure to particulate matter (PM) have been thoroughly investigated in humans and other model species, but there is a dearth of studies of the effects of PM on physiology and life-history traits of non-human organisms living in natural or semi-natural environments. Besides toxicological relevance, PM has been recently suggested to exert epigenetic effects by altering DNA methylation patterns. Here, we investigated for the first time the association between the exposure to free-air PM10 and DNA methylation at two loci ('poly-Q exon' and '5′-UTR') of the Clock gene in blood cells of the nestlings of a synanthropic passerine bird, the barn swallow ( Hirundo rustica ). The Clock gene is a phylogenetically highly conserved gene playing a major role in governing circadian rhythms and circannual life cycles of animals, implying that change in its level of methylation can impact on important fitness traits. We found that methylation at both loci significantly increased with PM10 levels recorded few days before blood sampling, and also with PM10 exposure experienced by the mother during or shortly before egg laying. This study is the first where methylation at a functionally important gene has been shown to vary according to the concentration of anthropogenic pollutants in any animal species in the wild. Since early-life environmental conditions produce epigenetic effects that can transgenerationally be transmitted, DNA methylation of genes controlling photoperiodic response can have far reaching consequences for the ecology and the evolution of wild animal populations. Graphical abstract: Highlights: DNA methylation according to airborne PM10 was examined in barn swallow nestlings. Methylation was measured on the Clock gene, which is involved in circannual activities. Methylation increased with PM10 level recorded few days before blood sampling. Methylation increased with PM10 level experienced by the mother during egg laying. Anthropogenic pollution may affect populations in the wild via epigenetic effects. Abstract : PM10 exposure increases DNA methylation at Clock gene in barn swallow nestlings.